2018
DOI: 10.1080/1343943x.2018.1428494
|View full text |Cite
|
Sign up to set email alerts
|

Water supply from pearl millet by hydraulic lift can mitigate drought stress and improve productivity of rice by the close mixed planting

Abstract: The authors have proposed the close mixed planting technique using mixed seedlings of two different crop species that results in close tangling of their root systems. Especially, the combination of drought-adaptive upland crops (e.g. pearl millet or sorghum) and flood-adaptive lowland crop of rice would be beneficial to overcome the drought and flood conditions and to reduce the risks of crop failure. In our previous studies, we found that upland crop yield losses by flood stress was mitigated by mix-cropped r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The degree to which such processes contribute to the agronomically proven positive effects on millet and cowpea in Ziziphus-based cropping systems remains to be explored (Bado et al 2020). Hydraulic equilibration in intercropping deeper and shallower rooted plants (Kizito et al 2012;Izumi et al 2018) has been portrayed as 'bio-irrigation' (Bogie et al 2018). It depends, however, on conditions where deeper soil water reserves are replenished during episodes with temporary rainfall excess over evapotranspiration (van Noordwijk and Ong, 1999;van Noordwijk et al 2014).…”
Section: Current State Of the Artmentioning
confidence: 99%
“…The degree to which such processes contribute to the agronomically proven positive effects on millet and cowpea in Ziziphus-based cropping systems remains to be explored (Bado et al 2020). Hydraulic equilibration in intercropping deeper and shallower rooted plants (Kizito et al 2012;Izumi et al 2018) has been portrayed as 'bio-irrigation' (Bogie et al 2018). It depends, however, on conditions where deeper soil water reserves are replenished during episodes with temporary rainfall excess over evapotranspiration (van Noordwijk and Ong, 1999;van Noordwijk et al 2014).…”
Section: Current State Of the Artmentioning
confidence: 99%
“…Hydraulic lift has other side benefits such as higher fine root survival (Bauerle et al 2008), a limited root embolism during the day by refilling xylem conduits at night (Domec et al 2004(Domec et al , 2006Prieto and Ryel 2014) or improved soil nutrient recycling that could benefit both the woody species and associated crops (Aanderud and Richards 2009;Armas et al 2012;Cardon and Gage 2006;Cardon et al 2013;Prieto et al 2012a). For neighboring plants, water that is redistributed to shallow soil layers can also be taken up by plants living in close association to plants engaged in HL enhancing their transpiration and ultimately increasing their survival and biomass production (Bogie et al 2018;Izumi et al 2018;Lee et al 2018;Prieto et al 2011). Nevertheless, the net effects that species engaged in HR have on their neighbors is still unclear (Prieto et al 2012b).…”
Section: Water Sharing and Redistribution By Rootsmentioning
confidence: 99%
“…Several studies have shown that HL enhances water availability to plants (McMichael and Lascano 2010;Hirota et al 2004;Prieto et al 2011;Shen et al 2011;Smart et al 2005;Wan et al 2000), thereby promoting microbial processes and decomposition processes which release nutrients from organic matter and soil minerals (Aanderud and Richards 2009;Armas et al 2012;Austin et al 2004;Cardon et al 2013;Matimati et al 2014;Munoz et al 2008;Prieto et al 2012a;Smith et al 1999;Yoder and Nowak 1999) that could also benefit the growth and survival of plant neighbors. The process of HL may therefore contribute significantly towards meeting the water, and or nutrient supplies needed to support growth and grain filling in associated crops in agroforestry systems with limited water availability (Bogie et al 2018;Izumi et al 2018). The potential application and exploitation of HL to improve water availability to crops or seedlings/saplings in forestry and ecological restoration has been already suggested (Burgess 2011; Liste and White 2008) but, to date, real-world experimental tests in agroforestry systems are still limited but show promising results.…”
Section: Water Sharing and Redistribution By Rootsmentioning
confidence: 99%
“…Academic interest in facilitation (positive, non-trophic interactions between physiologically independent plants) has increased over the past decades and there is good evidence that facilitative interactions are more common than was previously thought (Brooker et al 2008). Importantly, recent research has highlighted that such beneficial interactions can also be found in agricultural systems and could be central to the development of sustainable food production (Brooker et al 2015;Vincent et al 2017;Izumi et al 2018;Yin et al 2020).…”
Section: Introductionmentioning
confidence: 99%